Dampak Kepribadian Narsistik terhadap quality of work life dalam Era Hybrid Working - Rinda Kumala Wati; Indrayanti . (Psychopolytan : Jurnal Psikologi, 2024)
Hybrid working is the work model chosen by many companies. In practice, changing your work style to a hybrid can affect the quality of work life. Quality of work life is an employee's perception which includes aspects of job and career satisfaction, general well-being, distance from homework, stress at work, control at work, working conditions. On the other hand, employee personality is a kind of diversity in the workplace. One of the personalities in the workplace is the personality of narcissism. Narcissism is part of the dark triad personality. Narcissism is demonstrated by behavior of self-admiration, domination, and superiority. The aim of this research is to explain the role of narcissistic personality in the quality of work life of employees who work in a hybrid manner. The participants were 217 hybrid working employees who filled out the Quality of work life and Short Dark Triad Personality scale instruments. The participants consisted of government agency employees, male and female, private employees, government agencies and start-ups, ranging in age from 20 to 55, with D3 to S3 educational backgrounds. Participants were selected using a purposive sampling method. The research results show that narcissistic personality plays a role in the quality of work life (b=0.055; p<0.001). Companies need to manage narcissistic traits through personnel management to improve the quality of work life in a hybrid work environment.